ASEP youth sport training kit - Human Kinetics (Firm) (Champaign, Illinois : Human Kinetics, 2008)
Coaching basic video series features everything a coach needs to know to coach youth sports succesfully, winning respects introduces athletes to important concepts of winning respects both inside and outside the sport arena, sports parent presents real kids discussing their parents' involvement in their sport program and officiating youth sport features experienced sport officials sharing their expertise to help new or novice officials learn the fundamentals of officiating and how to be an effective official
Program 1. Coaching basics: being a C.O.A.C.H. - Program 2. Coaching basics: preparing for game day - Program 3. Coaching basics: coaching safety - Program 4. Winning respect - Program 5. SportParent - Program 6. Officiating youth sport
Title from container
American Sport Education Program (ASEP), a division of Human Kinetics
DVD format
Keywords: Sports for children; Sports for children -- Coaching; Parent and child